PERTANGGUNGJAWABAN PIDANA PELAKU JUAL BELI KONTEN PORNOGRAFI PADA MEDIA SOSIAL TWITTER - Krisma (UM-Tapsel Press, 2021)
The advances in information and communication technology have given birth to many things, one of which is social media. In addition to interacting, social media can also be used to carry out trading activities for goods and services. However, it turns out that there are buying and selling activities that are not properly traded, namely pornographic content. This activity is mostly found on Twitter. The pornographic content are the photos and videos of Twitter users themselves which contain obscenity and offer other Twitter users to buy their private content. This is a criminal offense prohibited by Indonesia law. This study will use a normative juridical research method that is descriptive analytical using secondary data with some legal materials. It is hoped that this research can be useful for people to be aware of the law so they do not commit that kind of criminal act in the future.